EXPERIMENTAL AND COMPARATIVE STUDY OF OPTICAL PROPERTIES OF DIFFERENT PHANTOMS BY THE KUBELKA-MUNK FUNCTION APPROACH - Durmus, Huseyin Okan; Karaboce, Baki; Seyidov, MirHasan Yu (Springer, 2023)
We optically characterized agar, muscle, and Zerdine phantoms mimicking human tissues. To the best of our knowledge, optical parameters for agar, muscle, and Zerdine phantoms have not been optimally determined in the literature. For this reason, this novel study makes signifi cant contributions to the literature and there is an important innovation and originality in the optical characterization of these materials. With this research based on the phantoms, in this article we make important contributions to possible future studies, including optical device design and imaging technique development, system validation studies, etc. In other words, characterization studies on materials that imitate tissue in light- tissue interactions can provide important information to researchers and practitioners. In optical characterization, basic parameters such as the absorption coefficient, reduced scattering coefficient, and anisotropy factor, are evaluated as distinguishing characteristics, and these are referred to as microscopic optical properties in the literature. In this study, the optical properties of the aforementioned three different phantoms were experimentally investigated and compared with each other's. First, the macroscopic optical properties of the phantoms, including the absorbance, transmittance, reflectance, refractive index, and attenuation coefficient, were measured using a single integrated sphere and a spectrometer equipped with a broadband white light source within the wavelength range 200 to 1000 nm. Then, using the Kubelka-Munk function method, microscopic optical properties, which are the absorption coefficient, scattering coefficient, and reduced scattering coefficient, were determined based on the data of these macroscopic properties.
Keywords: agar; Zerdine; and muscle phantom; microscopic and macroscopic optical properties; spectrometer; single integrating sphere; broadband white light source